Three-Dimensional Model of Sub-Plasmalemmal Ca2+ Microdomains Evoked by T Cell Receptor/CD3 Complex Stimulation - Gil, Diana; Diercks, Björn-Philipp; Guse, Andreas H.; Dupont, Geneviève (Frontiers in Molecular Biosciences, 2022)
Ca2+ signalling plays an essential role in T cell activation, which is a key step to start an adaptive immune response. During the transition from a quiescent to a fully activated state, Ca2+ microdomains of reduced spatial and temporal extents develop in the junctions between the plasma membrane (PM) and the endoplasmic reticulum (ER). These microdomains rely on Ca2+ entry from the extracellular medium, via the ORAI1/STIM1/STIM2 system that mediates store operated Ca2+ entry (SOCE). The mechanism leading to local store depletion and subsequent Ca2+ entry depends on the activation state of the cells. The initial, smaller microdomains are triggered by D-myo-inositol 1,4,5-trisphosphate (IP3) signalling in response to T cell adhesion. TCR/CD3 stimulation then initiates NAADP signalling, which activates ryanodine receptors (RYR). We have recently developed a mathematical model to elucidate the spatiotemporal Ca2+ dynamics of the microdomains triggered by IP3 signalling in response to T cell adhesion (Gil et al., 2021). This reaction-diffusion model describes the evolution of the cytosolic and ER Ca2+ concentrations in a three-dimensional ER-PM junction and was solved using COMSOL Multiphysics. Modelling predicted that adhesion-dependent microdomains result from the concerted activity of IP3 receptors and pre-formed ORAI1-STIM2 complexes. In the present study, we extent this model to include the role of RYRs rapidly after TCR/CD3 stimulation. The involvement of STIM1, which has a lower KD for Ca2+ than STIM2, is also considered. Detailed 3D spatio-temporal simulations show that these Ca2+ microdomains rely on the concerted opening of ~7 RYRs that are simultaneously active in response to the increase in NAADP induced by T cell stimulation. Opening of these RYRs provoke a local depletion of ER Ca2+ that triggers Ca2+ flux through the ORAI1 channels. Simulations predict that RYRs are most probably located around the junction and that the increase in junctional Ca2+ concentration results from the combination between diffusion of Ca2+ released through the RYRs and Ca2+ entry through ORAI1 in the junction. The computational model moreover provides a tool allowing to investigate how Ca2+ microdomains occur, extent and interact in various states of T cell activation.